Bamboo Fiber Composites: Characteristics, Manufacturing Processes, and Versatile Applications - A Review - Al Ichlas, Imran; Raden Rinova, Sisworo; La, Hasanuddin; Janviter, Manalu; Johni Jonathan, Numberi; Apolo, Safanpo (INTI International University, 2023)
Naturally occurring bamboo fibers, recognised for their environmentally sustainable characteristics, are gaining recognition as desirable natural fibers for composite materials. This review article provides an in-depth investigation of bamboo fibers, including their distinctive attributes, the diverse manufacturing techniques employed for fabricating of bamboo fiber-enhanced composites, the physical and mechanical properties of these composites, and their extensive array of applications. Bamboo fibers possess numerous advantages, including high strength, rigidity, resistance to corrosion, biodegradability, wide accessibility, affordability, and flexibility. The surface treatment of bamboo fiber is crucial for enhancing the adhesive strength, minimising water absorption, enhancing mechanical properties, ensuring uniform distribution of fibers, and enhancing resistance to deterioration. Consequently, bamboo fiber becomes an exceptional constituent for diverse industrial applications. Comprehending each manufacturing technique, together with its merits and drawbacks in relation to a particular application, can aid in selecting the suitable process for manufacturing composite materials with the needed performance. Bamboo fiber-enhanced composites provide outstanding attributes that make them highly promising for applications in the building, food packaging, transportation, and energy sectors